European Consumers’ Perceptions of Chinese Smartphone Brands: At the Intersection of Nation Brand Image, Country-of-Origin, and Product Brand Image - Nidhi,Adithya; Awalianti,Aqmarina; Irawan,Fakhri (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose: To investigate how the nation brand and country-of-origin of China jointly influence the European consumers’ perceptions towards Chinese smartphone brands. The reputation of Chinese smartphone brands in Europe is shaped by European consumers' concerns about China's national image over their global success and technological advancements. Hence, this study focuses on how these perceptions influence the products’ brand image. Design/methodology/approach: This descriptive-explanatory study uses a qualitative approach, using semi-structured in-depth interviews with seven students from Lund University, Sweden, representing six European nationalities. The data were thematically analysed to identify the key themes on nation branding, country-of-origin branding, and consumer perceptions or brand image. Findings: This study revealed that European consumers’ perception of Chinese smartphone brands is shaped by China’s nation branding and country-of-origin. Brands that have strong links with Chinese names associated with imitating Apple, have data privacy problems, and government control. Meanwhile, brands that are not Chinese sound perceived as more positive and less affected by China’s politics. Research limitations/implications: Small samples of young European consumers were used in this study, which limits the broad applicability of the findings. Broader and more diverse cross-cultural research is needed for the validation of these results. Practical implications: This research offers valuable insight and suggestions for Chinese smartphone brands to establish a stronger and unique brand identity, as well as communicate data ethics clearly to enhance consumer trust and global appeal in the European markets. Originality/value: This study contributes to the incorporation of country-of-origin and nation branding in shaping the perception of a product brand image. This study further enriches the previous research by proposing a framework that demonstrates an integral part between nation brand, country-of-origin branding, and product brand image moderated by brand identity.
Keywords: Nation Brand; Country-of-Origin; Source-of-Origin; Brand Identity; Brand Image; Chinese Smartphone Brands; Consumer Trust; European Market; Perception; “Made in China”